Association of Klotho Gene Polymorphisms with Type 2 Diabetes Mellitus: KL Gene Polymorphisms and T2DM - Mudassar, Sahar; Sarfraz, Abubakar; Shahid, Amina; Ahmad, Ejaz; Joher, Imran; Anam, . (Pakistan Journal of Health Sciences, 2025)
Genetic variants in the Klotho gene could influence the way β-cells function and effectively glucose functions, and this might influence the development of Type 2 Diabetes Mellitus. Objectives: To investigate the association between Klotho gene polymorphisms rs677332 and to determine the risk of developing type II diabetes in a case-control study. Methods: This case-control study was conducted from Feb 2024 to July 2024 at the Department of Pathology, Rashid Latif Medical College, Lahore. The total number of participants was n=586, sample n=293 case diabetics and 293 controls. DNA was extracted from blood samples and genotyped using Polymerase Chain Reaction followed by restriction digestion and validated through Sanger sequencing. To evaluate the genetic and clinical data, statistical tests were performed with SPSS version 25.0 and PLINK (v1.07). Logistic regression analysis, adjusted for age, sex, and region, was used to determine associations between Klotho polymorphisms and Type 2 Diabetes Mellitus. Fasting blood glucose levels were used as a reference variable in multiple nominal regression. Results: The SNPs rs677332 polymorphism and type 2 diabetes were significantly correlated, underscoring the importance of age, BMI, and heredity in diabetes risk. Logistic regression confirmed that individuals in the AA genotype were linked to a 73% rise in the likelihood of diabetes (OR=1.73, p=0.004). Conclusions: The rs677332 polymorphism of the Klotho gene may serve as a potential protective factor against Type 2 Diabetes Mellitus. The outcomes report the significance of Klotho gene variants for metabolic health and indicate the possible advantages of genetic screening for early treatment